Who Are Charter School Teachers? Comparing Teacher Characteristics, Job Choices, and Job Preferences - Cannata, Marisa Ann; Penaloza, Roberto (Education Policy Analysis Archives, 2012)
Given the importance of teachers to student learning, it is important to understand how and why charter schools differ in terms of their human capital. This paper explores the following questions: How do teacher qualifications and characteristics vary across school types? How much choice do teachers feel they have about where to work? How do teacher preferences for where to work differ by school type? Our findings suggest that charter school teachers do have different preferences for where to work compared to traditional public school teachers, but understanding these differences requires exploring differences among types of charter schools as well.